Acts of Passage: Women Writing Translation in Canada - Capperdoni, Alessandra (TTR)

(untitled) (Association canadienne de traductologie, 2007)
AbstractThis article discusses the relationship of writing and translation in Canadian feminist poetics, specifically experimental. As feminist poetics collapsing the boundaries between theory and creative act, “writing as translation” is a mode of articulation for female subjectivity and a strategy for oppositional poetics. The article engages with the practice of “writing as translation” in the works of two leading avant-garde artists, the francophone Nicole Brossard and the anglophone Daphne Marlatt, located respectively in Montreal and Vancouver. Building on the groundbreaking critical work of Barbara Godard, Kathy Mezei and Sherry Simon, it situates these practices in the socio-political and intellectual context of the 1970s and 1980s, which witnessed the emergence of women’s movements, feminist communities and feminist criticism, and in relation to the politics of translation in Canada. This historicization is necessary not only to understand the innovative work of Canadian feminist poetics but also the political dissemination of a feminist culture bringing together English and French Canada.